A unique predator in a unique ecosystem: modelling the apex predator within a Late Cretaceous crocodyliform‐dominated fauna from Brazil. Issue 2 (7th April 2020) - Montefeltro, Felipe C.; Lautenschlager, Stephan; Godoy, Pedro L.; Ferreira, Gabriel S.; Butler, Richard J.
Abstract: Theropod dinosaurs were relatively scarce in the Late Cretaceous ecosystems of southeast Brazil. Instead, hypercarnivorous crocodyliforms known as baurusuchids were abundant and probably occupied the ecological role of apex predators. Baurusuchids exhibited a series of morphological adaptations hypothesized to be associated with this ecological role, but quantitative biomechanical analyses of their morphology have so far been lacking. Here, we employ a biomechanical modelling approach, applying finite element analysis (FEA) to models of the skull and mandibles of a baurusuchid specimen. This allows us to characterize the craniomandibular apparatus of baurusuchids, as well as to compare the functional morphology of the group with that of other archosaurian carnivores, such as theropods and crocodylians. Our results support the ecological role of baurusuchids as specialized apex predators in the continental Late Cretaceous ecosystems of South America. With a relatively weak bite force ( 600 N), the predation strategies of baurusuchids likely relied on other morphological specializations, such as ziphodont dentition and strong cervical musculature. Comparative assessments of the stress distribution and magnitude of scaled models of other predators (the theropod Allosaurus fragilis and the living crocodylian Alligator mississippiensis ) consistently show different responses to loadings under the same functional scenarios, suggesting distinct predatory behaviors for these animals. The unique selective pressures in the arid to semi‐arid Late Cretaceous ecosystems of southeast Brazil, which were dominated by crocodyliforms, possibly drove the emergence and evolution of the biomechanical features seen in baurusuchids, which are distinct from those previously reported for other predatory taxa. Abstract : In this study we characterized biomechanically the skull of a fossil crocodyliform of the group Baurusuchidae using the finite element analysis (FEA). We compared our findings to cranial models of a theropod dinosaur and a living crocodylian. Our results suggest that baurusuchids present unique set of cranial adaptations not previously described for any group of predators.